Study on the Effect and Application Value of Heat-Inactivated Serum on the Detection of Thyroid Function, Tumor Markers, and Cytokines During the SARS-CoV-2 Pandemic - Xu, Enjun; Li, Tao; Chen, Qiuli; Wang, Zhongxin; Xu, Yuanhong (Frontiers in Medicine, 2021)
Purpose: The current explored the impact of heat inactivation of blood samples on the results of a particular clinical test and its potential application value during the SARS-CoV-2 pandemic. We have aimed at providing a reference for clinical testing methods during the pandemic. Methods: Blood samples were selected from our department's routine clinical examination between January 2021 and June 2021. The levels of these samples for quantitative detection of these indicators in each group (n = 90 cases/group) covered normal reference ranges and medically determined levels. For qualitative testing of the indicators, the specimens were additionally classified as negative, weakly positive, and positive (n = 20 cases/group). The specimens were then inactivated, and the differences in relevant indicators before and after inactivation were evaluated. Results: A statistically significant difference was evident between the levels of TSH, T3, FT4, FT3, AFP, NSE, CYFRA211, IRI, IL-1β, IL-6, IL-8, IL-10, IL-2R, and TNF-α in the non-inactivated group 1 and the inactivated group 1 (P < 0.05). Among them, there was a strong correlation between TSH, T3, FT4, FT3, CYFRA211, IRI, IL-1β, IL-6, IL-8, and IL-2R levels in the two groups (P < 0.05), however, there was no correlation between AFP (P = 0.256) and NSE (P = 0.352) levels between the two groups (P > 0.05). The detected values of low-level AFP (<4 ng/mL), IL-10, and TNF-α after inactivation were all lower than the detection limit. There was not any statistically significant difference in the levels of tumor markers, such as CEA, CA125, CA724, CA199, CA153, and the quantitative levels of T4, Vit. D, HCG, CPS, and five items of hepatitis B virus (P > 0.05). The positive rate of anti-nuclear antibodies after inactivation was not statistically different from the ones observed before inactivation (P > 0.05). Upon correction by the regression equation, the observed levels of TSH, T3, FT4, FT3, CYFRA211, IRI, IL-1β, IL-6, IL-8, and IL-2R were not significantly different from those before inactivation (P > 0.05). Conclusion: The heat inactivation of blood samples had different various effects on different test indicators, and some indicators could be corrected by employing regression equations. This detection method could potentially be employed during the SARS-CoV-2 pandemic, thereby effectively preventing iatrogenic infections.